Implementasi Pendekatan English Through Play untuk Meningkatkan Minat Bahasa Inggris pada Anak Usia 4–6 Tahun di Samantha English Course - Kresna Ningsih Manik; Siti Aisah Ginting (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
Early English mastery is a long-term educational investment that should be supported by instructional approaches aligned with children’s developmental characteristics. This community service program aimed to systematically implement the *English Through Play* approach, enhance English learning interest, and create positive learning experiences for children aged 4–6 years at Samantha English Course. The program was conducted participatorily through preparation, implementation, and evaluation stages over eight weeks. The *English Through Play* approach was applied through various activities, including action songs, flashcard games, storytelling with gestures, and simple role play. Evaluation was carried out descriptively through observation of participation, verbal responses, children’s expressions, and simple oral tests to measure basic vocabulary mastery. The results showed that more than 80% of the children were actively engaged during the learning sessions. Approximately 70–85% demonstrated increased learning interest, as reflected in their enthusiasm, verbal participation, and positive responses to English instructions. In addition, most children were able to recognize and pronounce 5–10 basic vocabulary items based on the learning themes and perform simple self-introductions. The program also produced a play-based learning guide that can be sustainably implemented by the partner institution. In conclusion, the *English Through Play* approach proved effective in enhancing young learners’ interest and participation in early English learning. This model can serve as a practical and replicable alternative for similar non-formal educational institutions.